Gore Mediation and the Bromance of Jair Bolsonaro and Donald Trump - Felinto, Erick; Grusin, Richard (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2021)
This article compares Donald Trump’s and Jair Bolsonaro’s strategies of governance in terms of what we define here as “gore mediation.” Gore mediation is the use of different electronic media in order not only to communicate political positions but also to terrorize people into accepting exclusionary policies and discriminatory practices. The creation of artificial threats and the dismissal of real ones (like the COVID pandemic) characterizes the actions of both Trump and Bolsonaro, whose governments operate fundamentally on symbolic bases, but whose incessant print, televisual, and networked mediations have violent socio-economic consequences.